Application of Learning Model Strategies to improve Islamic Learning Outcomes - Akrim, Akrim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the learning process of Islamic religious education in junior high schools. This study uses qualitative research, with the phenomenological approach of Al-Ulum MedanJakarta Integrated Islamic Middle School. Data collection techniques used in this study were observation, interviews, focus group discussions and documentation and then analyzed descriptively with an interactive analysis model. The results obtained are modeling learning strategies that have a good impact on improving student learning outcomes, by making some characters become models who practice certain materials in the learning process, so learning to dance from opening, core activities to closing. The conclusion of this study is the modeling learning strategy designed by the Al-Ulum Integrated Islamic Middle School to be superior and integrated characteristics of a junior high school, modeling learning strategies pay attention to the interests of students, the learning outcomes of Islamic religious education taught with modeling learning strategies are higher than those taught with conventional learning strategies.